Model development of an automatic safety control system for tower cranes when exposed to wind loads using the CodeSys integrated software - Safarov I.U; Kushakov M.M; Kamolov A.A (European Journal of Life Safety and Stability (2660-9630), 2021)
The article describes the development of a model of an automatic safety control system for tower cranes against the impact of a wind load using the complex CodeSys software environment.